CLINICAL AND MICROBIOLOGICAL DIAGNOSIS OF PLAQUE-INDUCED GINGIVITIS IN CHILDREN AND ADOLESCENTS - Hristina Tankova; Nadezhda Mitova; Zornitsa Lazarova (Peytchinski Publishing, 2022)
Aim: Clinical assessment of periodontal status and subgingival microflora in children aged 10-14 years with plaque-induced gingivitis. Materials and methods: The subject of the study were 34 children. The real-time PCR method was used for the identification of 9 subgingival microorganisms. Results: The studied children showed a probing depth averaging 1.26±0.24 mm and unsatisfactory oral hygiene (FMPS - 62.76±22.94). A generalized form of gingival inflammation was found with values of bleeding sites over 52% (BoP -52.76±17.57) and mild gingival inflammation (SBI - 1.17±0.73). C.gingivaliswas isolated in all children (100%), followed by P.intermediaand P.micros - in 70.6%. Microbial associations ranged from 2 to 8 microorganisms. Conclusion: Children aged 10-14 years are at risk for gingival inflammation because of the pronounced pathogenic potential of the subgingival microflora.